The Influence of Performance Accountability, Service Digitalization, Bureaucratic Reform on ASN Integrity through Work Commitment as a Mediation Variable in the Regional Personnel and Human Resource Development Agency in Brebes Regency - Moh. Charis Maulida; Gunistiyo; Mahben Jalil (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2021)
The State Civil Apparatus (ASN) must have the value of integrity so that it can prevent itself from attempts to abuse power or authority. Instilling the values of integrity and anti-corruption must be done as early as possible. Instilling the value of integrity from an early age makes government officials understand better that actions that conflict with the value of integrity are actions that are detrimental to the state. This value of integrity also directs ASN to act consistently and firmly in upholding the noble values and principles of life that it upholds. The subjectsiof thisistudy were BKPSDMD Civil Servants of Brebes Regencyiand the Head of General Affairs and Personnel Subdivision. Methods of data collection using a questionnaire. Test the validity and reliability using SEM (Structural Equation Modeling). The influence of performance accountability (X1), digitization of services (X2), bureaucratic reform (X3) and work commitment (Z) on integrity (Y) can be identified using regression techniques. Testing the mediation hypothesis can be done with the Sobel Test. The results of this study are expected to provide advice for the Brebes district government in providing effective handling that is able to solve existing problems and improve the integrity of ASN, so that ASN will be more optimal in carrying out their duties because they have good integrity.